'Look Out Behind You!' Grounding suspense in the slasher film. Issue 3 (3rd July 2017) - Coëgnarts, Maarten; Kiss, Miklós
Abstract: Suspense in cinema has often been described to result from either (1) the frustration of the viewers' strong desire to know the narrative's outcome (the uncertainty premise), or (2) the frustration of the viewers' strong desire to use their knowledge in order to change the narrative's outcome (the helplessness premise). In order to test the veracity of these assertions, one needs to examine the underlying mechanisms on which these cognitive frustrations (and by that the creation of suspense) rest. This paper aims to take on this task by drawing on the conceptual framework of Conceptual Metaphor Theory (CMT). Using the subgenre of the slasher film as an exemplary case study, we show how suspense is grounded in perception in which the spatial constituents of image schemas (e.g. front, back, light, dark) are instantiated cinematically (e.g. by framing, editing, lighting) in order to structure the narrative's conceptual constituents (e.g. the absence or presence of knowledge concerning the killer's whereabouts).